(untitled) (Journal of Health, Population and Nutrition, 2012)
On 13 May 2010, a cluster of diarrhoeal disease cases was reported among the inmates of a shelter-home for mentally-retarded females in Parbaksi village of Howrah district in West Bengal, India. The outbreak was investigated to identify the aetiological agent and source of infection and to propose recommendations. A suspected case of cholera was defined as an acute onset of ?3 loose watery stools in a female resident of the shelter-home since 1 May 2010. The demographic and clinical details were collected from the suspected case-patients, and the outbreak was described by time, place, and person. A retrospective cohort study was conducted to identify the risk factors associated with the illness. Of the 101 inmates, 91 (90%) developed diarrhoea, and three patients died (case fatality?3%). Four of the five stool specimens were positive for Vibrio cholerae O1 Ogawa. Drinking of water from the pond-connected tubewell (adjusted odds ratio=25.7, 95% confidence interval 2.7-236.4) was associated with the illness. Relocation of the pond-connected tubewell away from the groundwater tubewell, colour-coding of the tubewells meant for drinking purposes, and regular disinfection of the tubewells were recommended. DOI: http://dx.doi.org/10.3329/jhpn.v30i1.11290 J HEALTH POPUL NUTR 2012 Mar;30(1):109-112